If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 9 = 9 + -3x Reorder the terms: 9 + 6x = 9 + -3x Add '-9' to each side of the equation. 9 + -9 + 6x = 9 + -9 + -3x Combine like terms: 9 + -9 = 0 0 + 6x = 9 + -9 + -3x 6x = 9 + -9 + -3x Combine like terms: 9 + -9 = 0 6x = 0 + -3x 6x = -3x Solving 6x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6x + 3x = -3x + 3x Combine like terms: 6x + 3x = 9x 9x = -3x + 3x Combine like terms: -3x + 3x = 0 9x = 0 Divide each side by '9'. x = 0 Simplifying x = 0
| (50+-45x)+6=-6 | | 4r^2=4r-4 | | 3h-4k+7=3k-h | | m^2+3m=18 | | 2a^2=18a | | 5(10-9x)+6=6 | | 4(g+1)=2g-6 | | 12=4x-8 | | -12+48*67+4=x | | c-10c=0 | | 5r^2-43r+18=-6 | | 3x-3+2(2x)+13=-3-5x+(16-7) | | 2u^2-7u=4 | | -10c=0 | | 0.444w+6-0.333w=4 | | 2(x+1.1)=x+4.1 | | 2z^2+15x=0 | | 0.286y-0.833+0.714y=1.16 | | 3x+2[4-5(2x+1)]= | | y=8-2.5x | | 35=-3x^2-22x | | 5(t-2)=-10 | | 5+5y=55 | | 14-1.5x= | | -10(8n+-2)=60 | | -10(8n-2)=-60 | | -10=5(t-2) | | 9x-43=-30x-4 | | -10=5(-4-2) | | 4x-4+2(3x)+17=-3-3x+(16-7) | | 0=-16t^2+32t+12 | | (15+-5x)+-6=-19 |